Incentives Promoting Contracted Family Doctor Service Policy to Improve Continuity and Coordination in Diabetes Patient Management Care in China - Jin, Yinzi; Tian, Wenya; Yu, Yahang; Pan, Wen; Yuan, Beibei (Frontiers in Public Health, 2022)
Background: As the first step towards building a gatekeeping system in China, the governments have introduced a contracted family doctor service (CFDS) policy in primary healthcare (PHC) facilities. This study was to examine the association between apply of incentive to improve the implementation of CFDS and the performance on diabetes management care. Methods: We conducted a cross-sectional study in 72 PHC facilities in 6 cities that piloted the CFDS. Multivariate regression models were applied, based on a sample of 827 PHC providers and 420 diabetic patients. Results: PHC providers who reported the performance being linked with increased income were 168.1% and 78.0% more likely to have good continuity and coordination of diabetes patient management care, respectively. Additional one-point percentage of PHC providers whose performance on CFDS was assessed was associated with 7.192 times higher probability of patients with control of blood glucose. Discussion: Inclusion of incentives rewarding better performance on CFDS were associated with better delivery process and outcome performance on diabetes management care. Conclusion: Design and implementation of the incentive should be accompanied with the policy of CFDS, in order to increase the proportion of performance-related income of PHC providers, thereby improving the quality of diabetes management care.